Mapping of clinical management resources for snakebites and other animal envenomings in the Brazilian Amazon. (December 2022) - Beck, Timothy P.; Tupetz, Anna; Farias, Altair Seabra; Silva-Neto, Alexandre; Rocha, Thiago; Smith, Emily R.; Murta, Felipe; Dourado, Flavio Santos; Cardoso, Deugles; Ramos, Tatyana A.; Sachett, André; Pinto, Thiago Serrão; et al.
Abstract: Snakebite envenomings (SBEs) and other envenomings triggered by venomous animals (VAEs) represent a significant disease burden in Brazil, with 29, 152 SBEs reported in 2021 alone with nearly half of those occurring in the remote Brazilian Amazon. In 2021, Brazil recorded 240, 294 envenomings from snakes, scorpions, spiders, and caterpillars. Therefore, there is an unequal distribution of SBEs with high morbidity and mortality in the Brazilian Amazon. The severity of SBEs increases when patients require more than 6 h to access antivenom treatment, a common issue for the rural and indigenous populations. Understanding currently available resources and practices in Amazon remote areas of Brazil can serve to inform future interventions and guide health care policies. This study aims to develop a resource map of existing healthcare resources for the Brazilian Amazon's clinical management of VAEs with emphasis in SBEs, which will aid future strategic interventions. Data collection included a literature review, secondary data collected by government departments and organizational records, GIS mapping activities, and expert input. Our framework was guided by the three levels of healthcare service ecosystem analysis (macro, meso, and micro). Our resource map lays out a comprehensive overview of antivenom access, the distribution landscape, differences in patient transportation, and barriers to access healthcare that face populations in the Brazilian Amazon. Graphical abstract: Image 1 Highlights: In Brazil, there are financial, cultural, and logistical barriers to access antivenom. Despite antivenom manufacturing on a national scale, antivenom treatment is limited in rural areas. Indigenous and riverine populations are the most vulnerable to being deprived of proper treatment. We present a framework guided by the macro, meso, and micro levels of healthcare service. Antivenom treatment decentralization should be a priority of the health system in the Brazilian Amazon.